Comparative antioxidant effect of ascorbic acid and rosemary extract - E. K. Tunieva; V. V. Nasonova; N. M. Revutskaya (Теория и практика переработки мяса)
The aim of the work was to study an effect of ascorbic acid and the extract of rosemary on fat oxidation, color characteristics, pH and moisture binding capacity of minced pork during cold storage. The antioxidants were introduced into minced pork in an amount of 0.05%. After addition of the antioxidant, minced meat was packed in the modified atmosphere with the high oxygen content and stored at a temperature of 4 ± 2 ºС for 15 days. The indicators of the hydrolytic (acid value) and oxidative (peroxide value and thiobarbituric acid value) spoilage, color characteristics, pH and moisture binding capacity (MBC) were determined during the whole storage period (0, 5, 8, 12, 15 days). An increase in the acid value was recorded in all minced meat samples during storage without a significant difference between the control and experimental samples. Addition of the antioxidants led to a decrease in the peroxide value after 12 days of minced meat storage. Malonaldehyde began to accumulate in the control and the sample with ascorbic acid on the 8th day of storage and in the sample with the rosemary extract on the 12th day. The results obtained point to inhibition of fat oxidation in the minced meat samples with the antioxidants. Addition of the antioxidants facilitated an increase in redness compared to the control. Contrary to the rosemary extract, addition of ascorbic acid led to a decrease in pH and MBC of minced meat. Therefore, the use of the rosemary extract exerted more effective action of minced pork stability during storage compared to the same dose of ascorbic acid.